ANTROPOLOGERS OG INDFØDTE FOLKS FÆLLES VIRKELIGHED: Tre beretninger - Hasager, Ulla (Tidsskriftet Antropologi, 1996)
Ulla Hasager: The common reality of anthropologists and Indigenous peoples: three narratives The „traditional object" of anthropology - the indigenous peoples of the world - are becoming an increasingly visible global factor with the fourth world movements for self-determination and with the United Nations’ efforts to create standards for indigenous human rights. However, at the same time as the indigenous peoples are celebrated as guardians of environmental sustainability and biological and cultural diversity - and thereby for securing the memory as well as the future of mankind - their lands and resources are coveted by multinational corporations, govemments and other agencies, their genes are patented and preserved and their cultures are recorded - most often by anthropologists. In spite of these opposing trends and threats, indigenous peoples now have a more powerful position vis-å-vis anthropologists, who on their part are beginning to acknowledge the responsibilities that come with being part of the same living world as the indigenous peoples and therefore have begun the task of revising their theoretical foundations. Not only because they want to, but because the relatively more powerful and outspoken indigenous peoples demand it. This article looks at the changing situation for indigenous peoples in the Pacific, primarily Hawai’i, and outline the consequences for the conditions of research, methods of research and publication for anthropologists.